Effect of high Ni on battery thermal safety. (31st August 2020) - Wang, Dong; Zheng, Lili; Li, Xichao; Du, Guangchao; Feng, Yan; Jia, Longzhou; Dai, Zuoqiang
Summary: Frequent accidents involving Li‐ion batteries have prompted higher safety requirements for these batteries. In this study, the high‐temperature, thermal runaway (TR) characteristic parameters at 100% state of charge (SOC) for cylindrical NCM811 batteries with a high‐energy density were compared to the widely commercialized NCM523 batteries. The average TR trigger temperature of NCM811 battery was 157.54°C, which was 20.62°C lower than that of NCM523. Moreover, the average TR maximum temperature of NCM811 battery is 858.22°C, which was 212.81°C higher than that of NCM523. The maximum TR temperature of the NCM811 battery was 1289.53°C. The high Ni batteries exhibited poor thermal stability and severe TR. An increase in the Ni content resulted in increased fluctuations in the battery's internal TR reaction because high Ni batteries have a poor TR consistency and are difficult to accurately control. The TR combustion explosion of the fully charged NCM811 battery lasted for approximately 1.36 seconds. The combustion explosion severely damaged the positive electrode, and there was a collapse of the negative layered structure. The Cu current collector surface melted locally owing to the high temperature. Moreover, Ni, Co, and Mn particles appeared in the Cu current collectors and graphite.